2021
DOI: 10.23887/ijerr.v4i1.31565
|View full text |Cite
|
Sign up to set email alerts
|

Development of Picture Card Learning Media to Improve Sexual Understanding in Group B Kindergarten Children

Abstract: The rise of cases of sexual violence that occurs in minors causes victims to cause negative reactions such as shame, anger, hatred, offense, and psychological disorders. This study aimed to use picture card learning media to increase sexual understanding in early childhood. This type of research was development research. The model used in the study was the ADDIE model, which consisted of five steps, analysis, design, development, implementation, and evaluation. The techniques used in collecting data were obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The "SI ANDI -Siap Amankan Diri" flashcard games has a significant impact on developing early childhood's personal safety skills. This finding is consistent with previous research indicating that using flashcards as a learning tool can be effective in teaching sexual education (Widiarsini et al, 2021) as it enhances cognitive abilities in children (Fajriani et al, 2022;Saadah & Yulia, 2022;Utami, 2023). The interactive use of flashcards can stimulate children's enthusiasm and eagerness to learn (Herayanti et al, 2017;Sunismi, 2015).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The "SI ANDI -Siap Amankan Diri" flashcard games has a significant impact on developing early childhood's personal safety skills. This finding is consistent with previous research indicating that using flashcards as a learning tool can be effective in teaching sexual education (Widiarsini et al, 2021) as it enhances cognitive abilities in children (Fajriani et al, 2022;Saadah & Yulia, 2022;Utami, 2023). The interactive use of flashcards can stimulate children's enthusiasm and eagerness to learn (Herayanti et al, 2017;Sunismi, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Another approach to improving children's comprehension of personal safety skills is educational media through flashcard games (Anggreni et al, 2017;Nida et al, 2020;Widiarsini et al, 2021). Previous research results (Saadah & Yulia, 2022;Utami, 2023) have demonstrated that using flashcards can enhance children's cognitive abilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The process of improving self-quality in the world of education requires a variety of media. Media use can make educational activities more interesting and facilitate the individual's absorption of knowledge and information (Magta, 2022;Muhayat et al, 2017;Widiarsini et al, 2021). Media that is currently widely used is based on virtual reality technology.…”
Section: Introductionmentioning
confidence: 99%